2011
DOI: 10.1073/pnas.1018072108
|View full text |Cite
|
Sign up to set email alerts
|

Was the Devonian radiation of large predatory fish a consequence of rising atmospheric oxygen concentration?

Abstract: On the basis of a Mo-based geochemical proxy calibrated to the fossil record of fish, Dahl et al. argued that oxygen levels in the early Paleozoic were 15-50% of present atmospheric levels (PAL) and probably no more than a few percent PAL for the previous 2 billion years (1). It is an interesting result, but the study raised a number of issues.First, it is difficult to reconcile 15-50% PAL oxygen with the presence of Silurian charcoal, when ≈62% PAL oxygen is necessary to sustain wildfire (2).Second, the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Unlike mRNAs, lncRNAs are more often conserved of short sequence motifs or secondary structure and act as a molecular scaffolds that interact with multiple regulatory proteins [9]. For example, it was reported that NRON, as a molecular scaffold, is necessary for the assembly of NFAT and several NFAT kinases, which are responsible for NFAT phosphorylation and its sequestration in the cytosol [18]. In contrast, NKILA binding with NF-κB: IκB complex and masking the phosphorylation sites of IκB from IKK to inhibit the IKK-induced IκB phosphorylation [11], which was indirectly verified in NSCLC via RIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike mRNAs, lncRNAs are more often conserved of short sequence motifs or secondary structure and act as a molecular scaffolds that interact with multiple regulatory proteins [9]. For example, it was reported that NRON, as a molecular scaffold, is necessary for the assembly of NFAT and several NFAT kinases, which are responsible for NFAT phosphorylation and its sequestration in the cytosol [18]. In contrast, NKILA binding with NF-κB: IκB complex and masking the phosphorylation sites of IκB from IKK to inhibit the IKK-induced IκB phosphorylation [11], which was indirectly verified in NSCLC via RIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…A date of ~400 Ma for O 2 concentration attaining to 40% PAL (the minimum estimated requirement for predatory fishes above 1 m) was favoured when correlated against the low maximum length of Silurian gnathostomes (no taxa more than a few tens of centimeters) and the apparent rise of large predatory fishes, with presumably greater metabolic requirements, during the Devonian 1 . Although a simple causal relationship between size and hypoxia tolerance has been challenged 49 57 58 , extant marine fishes in general are also known to be less tolerant of hypoxic conditions than many marine invertebrates 1 56 59 . This suggests that low oxygen levels would have imposed some degree of extrinsic constraint on the maximum body size and available niche opportunities of the earliest gnathostomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the O 2 values presented by Berner () show no monotonic correlation with our maximum body size data (Spearman's r s < 0.5). The lack of correlation between changes in oxygen concentration and body size in cephalopods has been used to counter the link between rising atmospheric oxygen levels and giant body size in the Devonian (Butterfield ). Therefore, our data confirm that there is no simple correlation between body size and oxygen concentrations in Palaeozoic marine invertebrates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…latitudinal gradients in body size and the temperature-size rule; Bergmann 1847; Atkinson 1994Atkinson , 1996Angilletta et al 2004;Laptikhovsky 2006;Pincheira-Donoso et al 2008;Wilson 2009;Lee & Boulding 2010;Watt et al 2010). Not only the latitudinal distribution, but also the temporal distribution of giants in the fossil record has been discussed from an ecological perspective in support or against theories about the influence of major environmental changes in the geological past such as the oxygenation of the atmosphere and oceans (Payne et al 2009(Payne et al , 2011Dahl et al 2010;Butterfield 2011;Wei et al 2014). Palaeozoic invertebrate studies have focused on terrestrial arthropods (Dudley 1998;Harrison et al 2010;Clapham & Karr 2012), but their environmental requirements might be fundamentally different from those of aquatic (marine) invertebrates (Verberk et al 2011).…”
mentioning
confidence: 99%